The effect of feed transportation and an automatic feeding system on the physical and chemical quality of pelleted feed for broiler chickens Efecto del transporte y de un sistema automático de alimentación sobre la calidad física y química de los piensos granulados para pollos de engorde - Lorenzetti W.R.* (2019)
© 2019, UCOPress. Cordoba University Press (UCOPress Editorial Universidad de Córdoba). All rights reserved.The effects of feed transportation and the use of an automatic feeding system on chemical-physical characteristics of pelleted feed for broiler chickens at the final stage of production were evaluated. Samples were collected in two consecutive days and in two different poultry houses, both equipped with the same type of automatic pan feeding system. The samples were collected at the exit of the pelletizer dryer (PEL), at the exit of the bulk truck (CAM) and at 0 (LIN0), 50 (LIN50) and 100 (LIN100) meters of the feed line, for analysis of water activity, dry matter, mineral matter, crude protein, Embrapa Pelletizing Evaluation Method, Pellet Durability Index, as well as coarse and fine percentages. It was used a complete randomized block design (DBC) with five treatments (collection points) and five replicates each. The results indicate that the physical feed quality was negatively affected by transportation, with increased (P<0.05) water activity, fine particles (P<0.001) and mineral matter at the beginning of the feed line. There was no change in crude protein levels in the dry and natural matter of the diet (P>0.05). Feed truck unloading at the silo is the main factor affecting its physical quality causing greater pellet breakdown and de-mixing.